Effect of Bisphosphonates on Orthodontic Tooth Movement—An Update - Sindhuja Krishnan; Saravana Pandian; Aravind Kumar. S (Journal of Clinical and Diagnostic Research, 2015)
Bisphosphonates are a synthetic class of pyrophosphate analogues that are powerful inhibitors of bone resorption which are commonly used as a medication for the prevention and therapy of osteoporosis and osteopenia, also used to treat tumor diseases. As it affects bone metabolism, it is said to have an influence on orthodontic treatment and tooth movement. Also, this review gives an insight into the reported effects of Bisphosphonate medication in literature highlighting the status quo of scientific research regarding effects of Bisphosphonates on orthodontic tooth movement. A systematic literature search was done in Medline database (Pubmed) for the appropriate keywords. Manual handsearch was also done. From the available evidence it can be concluded that the duration of orthodontic treatment is increased for patients under Bisphosphonate therapy as they interfere with the osteoclastic resorption. However, they may be beneficial for anchorage procedures. Further long term prospective randomized controlled trials are required to assess possible benefits and adverse effects of bisphosphonate treatment, before Bisphosphonates can be therapeutically used in orthodontics.